THE SOLAR CIRCULATION CONCEPT: COMPARATIVE STUDY OF NICOLAUS COPERNICUS AND FAKHR AL-DĪN AL-RĀZĪ - Maisyatusy Syarifah (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2021)
This paper highlights how the concept of solar circulation according to Nicolaus Copernicus in On the Revolutions of the Heavenly Spheres Book and Fakhr al-Dīn al-Rāzī in Tafsīr Mafātīḥ al-Ghayb about the concept of solar circulation, and how are the similarities and differences about according to both of them. The study shows that Nicolaus Copernicus and Fakhr al-Dīn al-Rāzī agree that the sun is the center of the solar system, but they differ on three things, for example, Copernicus believes that the sun only stays in its orbit, while Fakhr al-Dīn al-Rāzī convinced that the sun goes around the earth, and so on. This study is library research with the descriptive-analytical method and comparative approach.